2002
DOI: 10.1080/13576500143000159
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric interaction and consciousness: Degree of handedness predicts the intensity of a sensory illusion

Abstract: It has been suggested that the two cerebral hemispheres play different roles in the maintenance and updating of an individual's beliefs. In particular it has been suggested that the left hemisphere (LH) forms consistent beliefs, whereas the right hemisphere (RH) monitors for inconsistencies or anomalies in reference to these beliefs. If some threshold of inconsistencies is detected, the role of the RH is to update the LH's belief system accordingly. Handedness may reflect the degree to which the two hemisphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 11 publications
3
60
0
Order By: Relevance
“…More importantly, with regard to interhemispheric interaction, research indicates that FS þ right-handers more closely resemble non-right-handers than they resemble FS-right-handers (Christman & Propper, 2001;Gorynia & Egenter, 2000;McKeever, VanDeventer, & Suberi, 1973). Niebauer and colleagues have reported that mixed-versus strong-handed differences are routinely enhanced when FS þ participants are excluded from analyses (Niebauer, 2004;Niebauer et al, 2002;. In addition to decreasing error variability, removing FS þ participants from a sample typically reduces the N by approximately 30-40%.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…More importantly, with regard to interhemispheric interaction, research indicates that FS þ right-handers more closely resemble non-right-handers than they resemble FS-right-handers (Christman & Propper, 2001;Gorynia & Egenter, 2000;McKeever, VanDeventer, & Suberi, 1973). Niebauer and colleagues have reported that mixed-versus strong-handed differences are routinely enhanced when FS þ participants are excluded from analyses (Niebauer, 2004;Niebauer et al, 2002;. In addition to decreasing error variability, removing FS þ participants from a sample typically reduces the N by approximately 30-40%.…”
Section: Resultsmentioning
confidence: 93%
“…Comparable findings reviewed earlier include those of Niebauer et al (2002), where people came into the lab believing that the fake arm was not theirs, but, given appropriate visual and tactile information, mixed-handers were more likely to change beliefs and assume ownership of the fake arm. Furthermore, as one's body size and shape changes, one would assume that (given appropriate input from oneself and others) one's body image beliefs would go hand-in-hand.…”
Section: Possible Mechanisms Of Handedness Differences In Interhemispmentioning
confidence: 87%
See 2 more Smart Citations
“…A similar result was reported by Nicholls et al (2005), although Jaspers-Fayer & Peters (2005) found no relationship between handedness and magical ideation, which was nevertheless more prevalent in females with a tendency to left-right confusion, perhaps suggestive of cerebral symmetry. In a similar vein, there is evidence that mixed-handedness is associated with a greater sensitivity to sensory illusions ( Niebauer et al 2002) and a higher risk of schizophrenia (Claridge et al 1998;Upadhyay et al 2004), and strong belief in the paranormal seems to be associated with symmetrical brain activity (Pizzagalli et al 2000). Jaynes (1976) speculated that cerebral asymmetry emerged in the second millennium BC, in response to assorted catastrophes, such as floods, invasions, etc.…”
Section: (B) Why the Variation In Lateralization?mentioning
confidence: 99%